(untitled) (Polifonia, 2020)
The fanfictional genre has not been extensively investigated in Brazil. In fact, there is very little academic work on this genre in universities (MYERS, 2006, MORLEY, 2007, BLYTHE & SWEET, 2008, HEALEY, 2009 and OBERHOLZER, 2014). Therefore, a Fanfictional Creative Writing in English course (FCWE) was developed and taught at the end of 2016. This course was attended by 5 undergraduate students in Languages and Literatures. Two of the objectives of this course were to 1) identify and 2) develop concepts about fanfictions. For this article, only student A was taken as an example. The methodology applied was the Case Study (DUFF, 2008, 2012; DYSON, 2005; STAKE, 2006). The FCWE course was based on the Vygotskian sociocultural theory (VYGOTSKY, 2004; 2007). As a result, student A demonstrated signs of development regarding social facts, speech acts, genre sets, and genre systems (BAZERMAN, 2012; CURRY & LILLIS, 2016).